COMPARING THE EFFECTIVENESS OF ASSAY FORMULATION FROM VARIOUS TRADITIONAL PLANTS AS PEDICULICIDE AGAINST Pediculus humanus capitis - Desy Rosalina Sari; Iman Surya Pratama; Galuh Tresnani (Sanata Dharma University, 2021)
Pediculosis capitis is an infection with a fairly high incidence in children. Plants that contain eugenol, as frangipani (Michelia champaca L.), ceylon ironwood (Mesua ferrea L.), cinnamon (Cinnamomum burmannii), and sugar apple (Annona squamosa L.) have potential as an alternative pediculicide. This study aimed to compare the effect of traditional formulation of each plant with in vitro assay. The effectiveness of in vitro pediculicide was assessed from the post- immersion mortality time of the traditional formulation, permethrin 1% as the positive control and coconut oil as the negative control. The mechanism was observed using histopathological observation. The percentage of mortality time of lice was analyzed using One-Way ANOVA of SPSS 16. Histopathological aspects and infestation decrease were presented descriptively. This study took place for about 3 months and was conducted in Mataram University, West Nusa Tenggara. The results showed that frangipani leaves had the optimum pediculicide effect because the highest efficacy demonstrated by frangipani leaves formulation revealed the effect lower than permethrin 1% (LT: 350 minutes). In observation of histopathology, frangipani leaves formulation indicated the presence of anoxia similar to permethrin 1%.